Potentials of organic amendments on yield attributes and protein content of rice - Mia, Md Harun; Saha , Mithun Kumar; Khan, Md Harunor Rashid (Dhaka University Journal of Biological Sciences, 2025)
A field experiment was carried out in Habiganj, Bangladesh, to evaluate the effects of various organic amendments, including rice straw plus cow dung composts (1:2 and 1:4 ratios), sawdust compost, rice husk compost, vermicompost, and tricho-compost on the yield attributes and protein content of BR 22 rice grown under natural field conditions. The experiment was structured with a completely randomized block design and included three replications. In subplots, organic amendments were applied at varying rates of 0, 5, and 10 tons per hectare. The application of these organic amendments significantly (p ≤ 0.05) improved various agronomic attributes of rice compared to the control plot. Tricho-compost (TC) at 5 and 10 t ha⁻1 ranked 1st and 2nd, respectively, in terms of tillers per hill (45 and 40 at the maximum tillering stage; 42 and 38 at harvest), productive tiller ratio (0.89 and 0.72), straw dry matter production (10.72 and 10.29 t ha⁻1), and grain yield (8.00 and 7.57 t ha⁻1). However, the highest protein content in grains (14.0%) was achieved with vermicompost at its higher dose (T3), followed by TC (T8) and rice husk compost (T13). The study concludes that locally available organic amendments of tricho-compost and vermicompost found to be significantly (p ≤ 0.05) improve rice yield and protein content, making them a viable option for sustainable rice production. Dhaka Univ. J. Biol. Sci. 34(1): 63-74, 2025 (January)